Uma nova espécie de Aniba (Lauraceae) da Amazônia - Kubitzki, Klaus (Acta Amazonica, 2020)
The Authors describe in this paper a new species of Lauraceae (Aniba lancifolia Kubitzki & Rodrigues), to date known only from the type locality in a rocky campina 130 Km. N of Manaus, Amazonas. This new species is remarkable for its shrubby habit and its broadly cordate leaf bases.